(Serious) new cook : recipes, tips & techniques - Quiroga, Leah Su; Lin, Cammie Kim (Rizzoli, 2022)
"Filled with recipes for impressive, craveable food--with all the guidance needed to make it--(Serious) New Cook is perfect for young adults or any new(ish) cooks who have ever found themselves salivating at cooking TikToks or drooling over gorgeous cookbooks, only to believe they aren't skilled enough to attempt the recipes themselves. Here, the clear, detailed instruction and stunning step-by-step photography will have readers wowing their friends and families from their very first dish"--